Decision making processes based on social conventional rules in early adolescents with and without autism spectrum disorders - Komeda, Hidetsugu; Osanai, Hidekazu; Yanaoka, Kaichi; Okamoto, Yuko; Fujioka, Toru; Arai, Sumiyoshi; Inohara, Keisuke; Koyasu, Masuo; Kusumi, Takashi; Takiguchi, Shinichiro; Kawatani, Masao; Kumazaki, Hirokazu; et al. (Scientific reports, 2016)
Autism spectrum disorder (ASD) is characterized by problems with reciprocal social interaction, repetitive behaviours/narrow interests, and impairments in the social cognition and emotional processing necessary for intention-based moral judgements. The aim of this study was to examine the information used by early adolescents with and without ASD when they judge story protagonists as good or bad. We predicted that adolescents with ASD would use protagonists’ behaviour, while typically developing (TD) adolescents would use protagonists’ characteristics when making the judgements. In Experiment 1, we measured sentence by sentence reading times and percentages for good or bad judgements. In Experiment 2, two story protagonists were presented and the participants determined which protagonist was better or worse. Experiment 1 results showed that the adolescents with ASD used protagonist behaviours and outcomes, whereas the TD adolescents used protagonist characteristics, behaviours, and outcomes. In Experiment 2, TD adolescents used characteristics information when making “bad” judgements. Taken together, in situations in which participants cannot go back and assess (Experiment 1), and in comparable situations in which all information is available (Experiment 2), adolescents with ASD do not rely on information about individual characteristics when making moral judgements.